Usage of the well-known plot in the twentieth century’s Russian drama - Головчинер, Валентина Е. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article by V. Golovchiner examines the usage of a well-known cultural material in the Russian drama. The author distinguishes three types among its formats in Russian drama of the twentieth century. V. Mayakovsky’s Mystery-Bouffe is represented as an explicit type of the well-known plot’s transformation. The type of drama with the implicit expression of the deep dramatic action layers or its components is presented in Mandate by N. Erdman. The play by G. Gorin Forget Herostratus! is an example of the third transformational type, in which the dramatist uses semantic associations with the name of the central character. The article analyses the strategies of using similar cultural transformations in the 20th century Russian drama.